Optimising the Compressive Behavior of Screw Piles in Sand for Marine Renewable Energy Applications - Jonathan A. Knappett; Michael J. Brown; Andrew J. Brennan; Lewis Hamilton (Deep Foundations Institute, 2014)
"Abstract This paper investigates the compressive behaviour of screw piles in sands and the key design parameters which control this. These types of foundation elements have typically been used as screw anchors onshore (i.e. for their tensile capacity), but there is increasing interest in their potential use as compression piles for supporting offshore marine renewable energy (MRE) devices (e.g. wind and tidal turbines) in deeper water. For such foundation applications, the compressive capacity is as important as the tensile capacity and is not well understood, particularly in cohesionless soils which are a likely seabed condition in MRE applications. A 1-g laboratory study was initially conducted on small scale model screw piles in sand beds of various relative density between 25 – 88%. These experiments were used to validate a Finite Element (FE) model having a stress-dependent constitutive model, making it useful for future up-scaling of the pile size for field applications. Following validation, the FE model was used to conduct a parametric study on the effects of flange spacing ratio (s/Dflange) and flange to shaft diameter ratio (Dflange/Dshaft). By using a validated FE model for this study, it was possible to observe the failure mechanisms (through the shear strain distribution) within the soil and correlate these with the pile capacity. This information was then used to comment on the most optimal (cost-effective) pile design for supporting compressive loads. This study represents a key step towards producing design tools appropriate for the design of screw piles in MREapplications.IntroductionAs defined in this paper, screw piles consist of a central small diameter hollow steel shaft, around which thin circular steel flanges run. Their principle of operation is that the flanges are spaced so as to trap the soil between them, thereby acting as an equivalent solid pile of the outer flange diameter, with a fully-rough ‘shaft’ interface (as shearing is soil-soil). One of the most important design decisions relates to the spacing of the flanges – if the flanges are spaced too far apart, then the soil will not be effectively trapped and the pile have a lower axial capacity and stiffness (controlled by the shaft friction along the central shaft and the bearing resistance arising from the individual flanges; If the flanges are spaced too close together, then there are potentially flanges which are not contributing to the pile capacity, therefore making the pile more expensive than it needs to be."